Biogeographic ranges do not support niche theory in radiating Canary Island plant clades - Steinbauer, Manuel J.; Field, Richard; Fernández-Palacios, José-Maria; Irl, Severin D.H.; Rüdiger, Otto; Schaefer, Hanno; Beierkuhnlein, Carl (Wiley, 2016)
Aim: Ecological niche concepts, in combination with biogeographic history, underlie our understanding of biogeographic ranges. Two pillars of this understanding are competitive displacement and niche conservatism. The competitive displacement hypothesis holds that very similar (e.g. closely related) co-occurring species should diverge, forced apart by competition. In contrast, according to the niche conservatism hypothesis, closely related species should have similar niches. If these are fundamental structuring forces, they should be detectable when comparing the climatic niches of endemic species in radiating clades in oceanic archipelagos, where closely related species exist in both sympatry and allopatry and the species' entire ranges are known. We took advantage of this natural experimental system to test whether the climatic niche relationships predicted by the two hypotheses are found.